Answer:
he variable term is zero so, the equation has no-solution
Step-by-step explanation:
Given as :
The two linear equation are
y = 3 x - 9 .........1
x - [tex]\dfrac{1}{3}[/tex] y = - 3 .........2
Now, , In substitution method we have to put the value of one variable from one equation into the other equation
Let put the value of y from eq 1 into eq 2
∵ x - [tex]\dfrac{1}{3}[/tex] y = - 3
Or, x - [tex]\dfrac{1}{3}[/tex] × ( 3 x - 9 ) = - 3
Or, x - [tex]\dfrac{3 x}{3}[/tex] + [tex]\dfrac{9}{3}[/tex] = - 3
Or, (x - x) + 3 = - 3
Or, 0 = - 3 + 9
Or, 0 = 3
∵ The variable term is zero so, the equation has no-solution Answer